Association of Knee Muscle Strength with Lower Extremity Dysfunction in Patients with Osteoarthritis: a Comparison with Rheumatoid Arthritis Patients and Healthy Controls - Yasemin ULUS,; Murat SAVLIK,; Yeşim Akyol,; Berna TANDER,; Ayhan BİLGİCİ,; Ömer KURU, (Archives of Rheumatology, 2013)
Objectives: This study aims to evaluate the relationship between knee muscle strength and lower limb dysfunction in patients with osteoarthritis (OA) in the lower limbs. Patients and methods: A total of 126 subjects including 42 with OA in the lower limbs, 42 with rheumatoid arthritis (RA) and 42 healthy controls (mean age 52.65±7.17 years; range 40 to 71 years) were enrolled. The lower limb pain of the patients was evaluated using the visual analog scale (VAS). All participants underwent an isokinetic knee muscle strength test, a six-minute walking test (6MWT), and the Rheumatoid and Arthritis Outcome Scale (RAOS). The disease activity scores involving 28 joints (DAS 28) of RA patients and the Kellgren-Lawrence scores of OA patients were recorded. Results: The pain intensity was similar in the OA and RA patients. There was no statistically significant difference among the three groups in terms of the 6MWT times. All of the RAOS subscales were significantly lower in the OA and RA patients compared to the control group (p<0.001), however, there was no statistically significant difference between the two patient groups. No significant difference in the isokinetic peak-torque (PT) ratio was observed among the groups. In the OA and RA patients, the VAS score was not correlated with none of the PTs, while the 6MWD showed a significant association with all PTs. Correlation and regression analyses revealed relationship between the PT measurements and a few RAOS subscales. There was no significant relationship between the PTs and DAS 28 in RA patients. No significant effects the radiological grade with regard to the 6MWD, RAOS subscales, and PTs were found in OA patients. Conclusion: Our study results demonstrated that a higher number of OA and RA patients with lower limb involvement have lower-limb dysfunction, compared to those without any rheumatological disorder. We conclude that the burden of the disease may be similar in OA and RA patients with lower limb involvement, which may have an adverse effect on the functional capacity of the patients.